The Assessment of Sustainable Tourism - Vargáné Csobán, Katalin (Acta Agraria Debreceniensis, 2005)
Tourism as one of the most significant sectors of the world economy plays an important role in achieving the goals of sustainable development. The fundamental conditions of sustainable development are the proper management of the environmental, social and economic impacts, as well as the well-established planning based on a detailed analysis. Measuring the changes and evaluating the results are tasks carried out by governmental and professional organizations. The first step of the assessment is defining the concept of sustainable tourism. Indicators are the most widely used set of tools for the assessment. Several international organizations have focused on elaborating the most suitable indicators for sustainable tourism development and formulating assessment models based on indicators since the beginning of the 1990s. Neither a generally accepted set of indicators nor a universally applicable assessment method has been put together until now. In the present study a few definitions of sustainable tourism are reviewed, criteria for indicator selection are listed, followed by the presentation of a sustainable tourism model. Finally a recently published assessment procedure based on the Bellagio Principles is summarized.